PENGARUH TINGKAT RELIGIUSITAS DAN KOMPENSASI FINANSIAL TERHADAP ETOS KERJA KARYAWAN PADA SALON MUSLIMAH HOUSE OF AISYA BOGOR - Sobari, Ahmad (STAI BHAKTI PERSADA BANDUNG, 2018)
House of Aisya is a special beauty house for Muslim women who care about birth and inner beauty. The House of Aisya Muslimah Salon has a mission to open jobs and introduce Muslim-inspired ethics by dedicating beauty care to Muslim women through halal and natural products, shar'i services, modern technology, and employees with work ethics in accordance with the teachings of Islam to realize birth satisfaction and inner Muslim women. The objectives of this study were: (1) The extent to which religiosity affects the work ethic of employees at the House of Aisya Bogor (2) How financial compensation affects the work ethic of employees in the House of Aisya Bogor. This study uses quantitative methods. Data collection techniques using questionnaires, while data analysis techniques using multiple linear regression analysis with the help of SPSS 23. The analysis shows that the significance value is 0.003, because 0.003 <0.05, H0 is rejected. So it can be concluded that the level of religiosity and financial compensation together affect the work ethic of employees at the Salon Muslimah House of Aisya Bogor. While partially it shows that the religiosity variable does not affect the work ethic of the employees at the Salon Muslimah House of Aisya Bogor and for the financial compensation variable it significantly influences the work ethic of employees at the Salon Muslimah House of Aisya Bogor.